PTU-005 Factors Influencing The Quality Of Colonoscopy Training In The North West Deanery. (9th June 2014) - Beejooa, G; Prasad, N; Shields, P
Abstract : Introduction: Endoscopy is integral to the JRCPTB Gastroenterology Curriculum and the JAG clearly defines competencies that must be achieved before independent practice. Training in colonoscopy for Gastroenterology Specialty Trainees (ST) can be challenging due to current work patterns and non-GI commitments. We aimed to evaluate the opportunities for and the quality of colonoscopy training in the NW Deanery as perceived by STs. Methods: An electronic questionnaire was sent to all Gastroenterology STs enrolled within the NW Deanery including questions based on data which would be available from the JETS e-portfolio. STs were excluded at the point of entering OOP activity. To allow comparison, number of procedures performed was standardised to year of training and to length of time in each post. We used an arbitrary minimum expected number of procedures per year at each level of training to calculate adequacy of training opportunities. Results: 29 trainees completed the survey (ST3=3, ST4=8, ST5=4, ST6=6, ST7=1, OOP = 7) at 13 sites. 7 (24%) had achieved JAG accreditation for diagnostic colonoscopy. Overall completion rate (CR) was 52.2% (0 to 97%). Mean number of colonoscopies (and independent CR) was: ST3=25.6 (7%), ST4=68.9 (19%), ST5=103.3 (65%), ST6=105.7 (87%), ST7=66 (92%). 5 (17%) STs had a CR of >90% and had performed an average of 270 procedures to attain this level. The average number of colonoscopies per year for each individual site ranged from 34% to 160% of expected procedures. 22 (76%) STs had used a scope guide and 33% of these STs found it useful. 62% of trainees were satisfied with the level of supervision during endoscopy. 62% of trainers had completed a TCT course or equivalent but 14% of STs did not know. The major limiting factor affecting colonoscopy training was GIM commitments (72%) with lists missed due to on call shifts. 41% reported that training lists were not tailored to their needs, 38% missed lists due to lack of ward cover and 38% did not feel that they had enough colonoscopy lists. Other factors affecting colonoscopy training included competition with nurse endoscopists (10%) and trainers taking over too early (14%). 24% of STs rated their satisfaction with colonoscopy training at 4 or 5 (on a scale of 1 to 5, where 1 was poor and 5 was excellent). Conclusion: There is considerable variability in opportunities and quality of colonoscopy training in the NW Deanery. Service provision must be balanced with a structured, high quality training programme to ensure that colonoscopy performance can meet the mandatory standards expected at the time of CCT. In our region, it is reassuring that STs seem to achieve these targets by ST7 despite the challenges we identified. This study provides a baseline for future quality improvement in NW Deanery colonoscopy training. Disclosure of Interest: None Declared.